Pekerja Prekariat dan Implikasi Atas Fleksibilitas Kerja di Kawasan Industri Kota Makassar - Nur Adhi, Rakhmat; AT, M Ramli; Muhammad, Sawedi (Universitas Muhammadiyah Sorong, 2023)
This research was conducted to explore the implications of work flexibility for precariat workers in Makassar City. The research was carried out with a qualitative approach and used a case study type of research on workers in the PKWT form or popularly known as contracts and outsourcing. The research location is in the Parangloe and KIMA Warehousing Areas. The method of determining informants was carried out by purposive sampling, so that there were 8 informants consisting of 4 outsourcing workers, 3 contract workers, and one HR worker from an outsourcing vendor. Data collection was carried out by in-depth interviews as the main method, in addition to observation and document collection which were considered important as secondary methods. The results of this study illustrate that there are several implications for implementing work flexibility for informants. First, the issue of job security is a priority for workers because there are a large group of reserve workers who are ready to replace them, forcing them to maintain their jobs even with a high workload but low wages. This also has implications for companies that find it easier to lay off workers and provide low wages to workers. The second implication is that workers are more likely to move between companies and jobs due to work flexibility. Frequent transfers also result in vulnerability due to uncertain wages and uncertainty about the continuity of work.